Sonochemical-Assisted Coprecipitation Synthesis of Body-Centered Tetragonal Mn3O4 Spinel Nanostructures Using Polyethylene Glycol Template Agent. Issue 1 (May 2019) - Hidayat, Nurul; Taufiq, Ahmad; Sunaryono; Chuenchom, Laemthong
Abstract: The excellent characteristics of Mn3 O4 nanomaterials have driven many experts to carry on exploring improved approaches for Mn3 O4 fabrication. Herein, Mn3 O4 nanostructures have been synthesized via sonochemical-assisted coprecipitation method. Polyethylene glycol (PEG-6000) with various concentrations was employed as a surface coating. The combination of coprecipitation and ultrasonication has led to the formation of Mn3 O4 nanoparticles which were well-confirmed by three different characterization instruments, i.e., X-ray diffraction (XRD), scanning electron microscopy (SEM) along with energy dispersive X-ray (SEM-EDX), and Fourier transform infrared (FTIR). The XRD data collection and analysis reveal the presence of single-phase of Mn3 O4 spinels. The Rietveld refinement dictates the establishment of tetragonal distortion along the c -axis creating a body-centered tetragonal spinel structure with a space group of I41/AMDS. In addition, the SEM-EDX and FTIR data support the experimental results obtained by XRD.